2021
DOI: 10.21776/ub.mnj.2021.007.01.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Level of Education and Post-Stroke Cognitive Status in Hospital-Based Ischemic Stroke Survivors

Abstract: Background: Post-ischemic stroke cognitive decline is significantly affecting the quality of life of its survivors. Its prevalence was about 7.5-72% which was mostly determined by the existing of vascular risk factors and cognitive reserve of the subjects. Level of education is one of determinants of cognitive reserve, a factor that affect the susceptibility of subjects to cognitive decline after experiencing ischemic stroke-related neuronal damage. Since level of education is protective for cognitive function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…19 A study conducted by Herpan Syafii Harahap et al mentioned that the level of education had a significant relationship with the impairment of post-ischemic stroke cognitive status among hospital-based ischemic stroke survivors. 20 Other factors that may affect the cognitive impairment were vascular risk factors. Based on a study conducted by Agnes Jacquina et al in France 21 , stroke patients who had hypertension (OR 2.36), diabetes mellitus (OR 3.57), atrial fibrillation (OR 2.68) were more likely to develop poststroke cognitive impairment.…”
Section: Sample Descriptionmentioning
confidence: 99%
“…19 A study conducted by Herpan Syafii Harahap et al mentioned that the level of education had a significant relationship with the impairment of post-ischemic stroke cognitive status among hospital-based ischemic stroke survivors. 20 Other factors that may affect the cognitive impairment were vascular risk factors. Based on a study conducted by Agnes Jacquina et al in France 21 , stroke patients who had hypertension (OR 2.36), diabetes mellitus (OR 3.57), atrial fibrillation (OR 2.68) were more likely to develop poststroke cognitive impairment.…”
Section: Sample Descriptionmentioning
confidence: 99%
“…These findings are in line with [ 14 ], in which in a nationally representative cohort of community-dwelling adults in the US, they found, after controlling for pre-stroke cognitive measures, that females, in contrast to males, experience post-stroke cognitive deficits, particularly during the early post-stroke period. In addition, recent studies in patients with ischemic stroke have identified that cognitive status and executive functions showed lower levels than would be expected for their age and education level [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%